Students’ Perception of Using Task-Based Learning in Teaching English for Business at Politeknik Madyathika - Fitriani, Artika Wina; Priyanto, Rofik; Paradista, Actinis Muqsitha (Absorbent Mind, 2025)
The English taught to students must have a specific purpose and intent. For business, English lessons require teachers to choose the right teaching method. This study explores students' perceptions of using task-based learning to teach English for Business at Polytechnic Madyathika Purbalingga. This study used a descriptive quantitative approach. Data were collected through questionnaires and interviews. The subjects of this study were 45 students of Polytechnic Madyathika Purbalingga. The results showed that students positively viewed using task-based learning in teaching English for Business. Students generally considered task-based learning an effective and engaging method for teaching English for Business. Its focus on real-world applications, communication skills, and collaborative learning aligns with the demands of the modern workplace. However, for TBL to reach its full potential, educators must address its challenges by providing adequate support and creating a welcoming environment for learners. Thus, TBL can play a vital role in preparing students for successful careers in business, equipping them with the language skills and confidence to excel in a competitive global marketplace.